Y balance test has no correlation with the Stability Index of the Biodex Balance System. (February 2017) - Almeida, Gabriel Peixoto Leão; Monteiro, Isabel Oliveira; Marizeiro, Débora Fortes; Maia, Laísa Braga; de Paula Lima, Pedro Olavo
Abstract: Study design: A cross-sectional study design. Background: The Stability Index of the Biodex Balance System (SI-BBS) and Y Balance Test (YBT) has been used in studies assessing postural stability but no studies have verified the association of the YBT with the SI-BBS. Objective: To analyze the association of the Y Balance Test (YBT) with the Stability Index of the Biodex Balance System (SI-BBS) to evaluate postural stability. Methods: Forty participants who engaged in recreational physical activities, 12 of whom had a history of injury to the lower limbs. Was used the SI-BBS and the anterior, posterolateral, posteromedial, and composite measures of the YBT. The order of execution of the tests and of the lower limbs evaluated was randomized and blind tested by two evaluators. Results: Pearson's correlation coefficient was used to check the strength of the relationship between the distances achieved on the YBT and the SI-BBS. The YBT showed excellent reliability in the anterior, posteromedial, and posterolateral directions. However, the YBT showed no statistically significant correlation with any variables in the SI-BBS, indicating poor validity between YBT and SI-BBS assessments of postural stability in people with and without history of lower limb injuries. Conclusions: The results of this study showed the YBT is not correlated with the SI-BBS as an assessment of postural stability. This finding has implications for researchers and clinicians using YBT results as the only measure of postural stability. Highlights: Y Balance Test and Biodex Balance System assess postural stability. There are no studies verifying the validity of YBT with Stability Index of the BBS. YBT showed good inter-examiner reliability. YBT showed poor validity with Stability Index of the BBS.